The long-term correlates of developmental stress on whole-brain functional connectivity during emotion regulation - Seda Sacu; Andrea Hermann; Tobias Banaschewski; Martin F. Gerchen; Nathalie E. Holz (Translational Psychiatry)
Abstract Early life stress is associated with alterations in brain function and connectivity during affective processing, especially in the fronto-limbic pathway. However, most of the previous studies were limited to a small set of priori-selected regions and did not address the impact of stress timing on functional connectivity. Using data from a longitudinal birth cohort study (n = 161, 87 females, mean age (SD) = 32.2(0.3)), we investigated the associations between different time points of stress exposure and functional connectivity. We measured stressful life events across development using a modified version of Munich Event List and grouped into four developmental stages: prenatal/newborn (prenatal-3 months), infancy and toddlerhood (3 months-4.5 years), childhood (4.5–11 years), and adolescence (11–19 years). All participants completed an fMRI-based emotion regulation task at the age of 33 years. Task-dependent directed functional connectivity was calculated using whole-brain generalized psychophysiological interactions. The association between life stress and connectivity was investigated within a multiple regression framework. Our findings revealed distinct associations between stress exposure and task-specific functional connectivity, depending on the developmental timing of stress exposure. While prenatal and childhood stress were associated with lower connectivity between subcortex and cognitive networks, stress exposure unique to adolescence was related to higher connectivity from the salience network to the cognitive networks. These results suggest that early life stress alters the connectivity of cognitive and limbic networks, which are important for emotion processing and regulation. Future research should replicate and extend the findings regarding sensitive periods by utilizing diverse paradigms in cognitive, social, and emotional domains.